ANALISIS TANTANGAN PENGEMBANGAN STRATEGI RUMAH SAKIT DALAM MENINGKATKAN MUTU PELAYANAN DAN DAYA SAING ORGANISASI: LITERARURE REVIEW - Dika Octaviani Yustedjo; Inggrid Green Nego; Monica Rizqi Yanuar Setyowati; Hotmada Parlindungan; Dhimas Dita Rahardian; Budi Hartono (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2026)
Background: Hospitals in the VUCA era face a dual imperative: maintaining social missions while ensuring financial sustainability. This complexity is exacerbated by the JKN shift to INA-CBGs, digital disruptions, and Law No. 17 of 2023 reinforcing corporate liability. Objective: This study analyzes challenges in strategy development and internal/external barriers to formulate recommendations for Indonesian hospital managers. Method: A Systematic Literature Review (SLR) with a descriptive-analytical approach was conducted on literature (2019–2025) from Google Scholar, PubMed, and SINTA, utilizing thematic synthesis and the Fishbone framework. Results: Findings reveal multidimensional internal barriers, including HR shortages, cultural resistance, and budget constraints. JKN implementation mandates a strategic shift from revenue generation to cost containment. While digital transformation is crucial for competitiveness, it faces infrastructure and cost hurdles. Furthermore, regulatory changes demand prioritized risk management due to heightened corporate liability. Conclusion: Strategic success depends on integrating operational efficiency, technological adaptation, and legal compliance. Adopting adaptive leadership, Lean Management, and robust risk management is recommended to maintain organizational competitiveness and sustainability